2020
DOI: 10.1039/d0cp00395f
|View full text |Cite
|
Sign up to set email alerts
|

Study of the surface species during thermal and plasma-enhanced atomic layer deposition of titanium oxide films using in situ IR-spectroscopy and in vacuo X-ray photoelectron spectroscopy

Abstract: By the powerful combination of in situ FTIR and in vacuo XPS, the surface species during ALD of TDMAT with different reactants could be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…In addition, the technique provides chemical information without the need of a high vacuum chamber to perform the measurement or the use of an irradiation source that might cause photo-oxidation of the azido-groups such as an UV- or X-ray irradiation. Furthermore, the degradation during the high vacuum treatment can be studied using in situ FTIR, which has previously been demonstrated to be a very sensitive technique to measure changes of chemical bonds at the surface …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the technique provides chemical information without the need of a high vacuum chamber to perform the measurement or the use of an irradiation source that might cause photo-oxidation of the azido-groups such as an UV- or X-ray irradiation. Furthermore, the degradation during the high vacuum treatment can be studied using in situ FTIR, which has previously been demonstrated to be a very sensitive technique to measure changes of chemical bonds at the surface …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the degradation during the high vacuum treatment can be studied using in situ FTIR, which has previously been demonstrated to be a very sensitive technique to measure changes of chemical bonds at the surface. 48 Silicon samples coated with 70 nm TiN and a 3 nm thin film of SiO 2 are used as the substrate for the N 3 −SAM deposition, to facilitate in situ reflection FTIR experiments. The TiN layer is deposited by reactive sputtering using nitrogen gas and a Ti target (Endura, Applied Materials Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…However, only with the help of in vacuo XPS can surface composition be accurately identified and quantified. Based on this, the mechanism of TiO 2 obtained from tetrakis­(dimethylamino)­titanium (TDMAT) in H 2 O vapor, H 2 O–plasma, or O 2 –plasma was investigated by combining in situ FTIR and in vacuo XPS by Vandenbroucke et al …”
Section: Mechanisms Of Ntps Modificationmentioning
confidence: 99%
“…Based on this, the mechanism of TiO 2 obtained from tetrakis(dimethylamino)titanium (TDMAT) in H 2 O vapor, H 2 O−plasma, or O 2 −plasma was investigated by combining in situ FTIR and in vacuo XPS by Vandenbroucke et al. 102 In situ FTIR was applied to detect the generation of surface species, such as imine and isocyanate during the deposition, while in vacuo XPS was used to identify surface groups (CO and NOx). These spectroscopic analyses were essential to provide quantitative information on the chemical composition, which enables researchers to analyze the plasmaenhanced ALD reaction mechanisms.…”
Section: Mechanisms Of Ntps Modificationmentioning
confidence: 99%
“…Ti[(CH 3 ) 2 N] 4 or Tetrakis(dimethylamido)titanium(IV) (hereinafter TDMAT) and water. Despite the significant number of publication reporting on TiO 2 ALD from TDMAT and water [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,31,33], there is no clear idea of all the possible chemical reactions on the surface during the growth process and also there is no unique behavior of growth curves (Growth Per Cycle) as a function of the growth temperature. Additionally, it was shown that the TiO 2 initial growth stages depend on substrate chemistry, as in the case of ZnO ALD [34,35,36,37], TiO 2 exhibit different types of growth depending on the surface [15,29].…”
Section: Introductionmentioning
confidence: 99%